2022
DOI: 10.1007/s10461-022-03819-x
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Soccer for Delivery of HIV and Substance Use Prevention for Young South African Men: 6-Month Outcomes of a Cluster Randomized Controlled Trial

Abstract: Young men in South Africa face the intersecting epidemics of HIV, substance use and endemic poverty. We tested the effectiveness of a behavioral intervention using soccer training to reduce the cluster of risks associated with HIV and substance use. This cluster randomized controlled trial was conducted with men aged 18–29 years old in 27 neighborhoods in the townships of Cape Town, South Africa. Neighborhoods were randomized to receive for 6 months either: (1) Soccer League (SL; n = 18 neighborhoods, n = 778 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…This is similar to previous scoping reviews that highlighted the diversity of approaches used to address men's mental health [1,33]. One intervention used physical activities such as soccer [26], four used online interventions [16,21,29,31], six corresponded to therapeutic counseling interventions including interview and cognitive behavior group treatment [8,15,27,[30][31][32], and one intervention used expert networks [5]. Thus, the majority corresponded to online and therapeutic counseling interventions.…”
Section: Overview Of the Identified Interventions And Effectiveness O...supporting
confidence: 81%
See 2 more Smart Citations
“…This is similar to previous scoping reviews that highlighted the diversity of approaches used to address men's mental health [1,33]. One intervention used physical activities such as soccer [26], four used online interventions [16,21,29,31], six corresponded to therapeutic counseling interventions including interview and cognitive behavior group treatment [8,15,27,[30][31][32], and one intervention used expert networks [5]. Thus, the majority corresponded to online and therapeutic counseling interventions.…”
Section: Overview Of the Identified Interventions And Effectiveness O...supporting
confidence: 81%
“…Therefore, it is necessary to confirm the effectiveness of the interventions applied to improve the mental health outcomes of men. Results of the study that applied soccer to the experimental group thrice a week, reported after six months that it was not effective in addressing various risk behaviors in young people, suggesting that early adulthood may be too late to change established risk-behavior [26]. Therefore, it is evident that the age of the participants must be considered when employing interventions such as sports that involve physical activities, though this needs to be confirmed through further research.…”
Section: Rct: Randomized-controlled Trials; *Protocol Development (Tr...mentioning
confidence: 99%
See 1 more Smart Citation
“…60 Efforts to address alcohol use and HIV risk have had mixed success, with evidence showing that social barriers (e.g., social norms around substance use) and structural level barriers (e.g., unemployment, poverty, violence, limited clinic resources) constrain long-lasting behavior change. 61,62 Building on these barriers for men, our data uncovered challenges that are exacerbated for and/or unique to South African migrants. Migrants may have a higher likelihood of life stressors, given the conditions that prompted their move as well as their near-universal need to find employment.…”
Section: Discussionmentioning
confidence: 99%
“…social norms around substance use) and structural‐level barriers (e.g. unemployment, poverty, violence, limited clinic resources) constrain long‐lasting behaviour change [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%